A rare case of melanoma erysipeloides - Mariem Rekik; Chaima Kouki; Nadine kammoun; khadija Sellami; Mariem Triki; Sonia Boudaya; Emna Bahloul; Mariem Amouri; Tahya Boudawara; Hamida Turki (Clinical Case Reports, 2022)
Abstract Malignant melanoma presenting as an inflammatory skin metastasis has been described but is an exceedingly rare phenomenon. We report a case of inflammatory metastasis of cutaneous melanoma (CM).